PENGARUH PEMBERIAN AKTIVITAS MERANGKAK TERHADAP KEMAMPUAN VISUAL-SPASIAL PADA ANAK DENGAN DOWN SYNDROME DI KLINIK A - Nurazizatul Arifah Zam; Handrix Chris Haryanto (Universitas Paramadina, 2019)
The purpose of this research was to see the effectivity of crawling on visual-spatial ability in child with down syndrome. This study is using single case experimental. The subject of this study is only one which is a child with down syndrome. The result of this study showed that crawling intervention made some effect such as increasing duration of response, but it was not significant. Therefore, this study is need to review for giving significant result that show crawling has been effective on visual-spatial ability for child with down syndrome.